Carbon Markets for Greenhouse Gas Emission Reduction in a Warming World : An Evaluation of the World Bank Group’s Support to Carbon Finance - Independent Evaluation Group (World Bank, Washington, DC, 2018)
Climate change is a threat to global development and to the core Mission of the World Bank Group. With the recognition that human activity drives global warming, the World Bank Group has pursued a long-term commitment to curb global greenhouse gas (GHG) emissions for more than 20 years. The purposes of this evaluation are to assess the role and contributions of the Bank Group in CF in relation to the needs and priorities of its client countries and its potential comparative advantages, and to draw lessons to inform the World Bank Group’s future strategic direction in CF. The evaluation aims to answer thefollowing overarching question: What has been the strategic objective, nature of engagement, and contribution of the Bank Group in supporting CF? What lessons can be drawn from this to inform the Bank Group’s strategic direction in supporting the next generation of marketbased carbon mitigation activities, given its potential comparative advantages?